Health service use of infants involved in family justice care and supervision proceedings in Wales: a data linkage study - Farr, Ian; Cowley, Laura; Broadhurst, Karen; Odd, David; Jones, Carys; Bailey, Grace; Alrouh, Bachar; Abouelenin, Mariam; Cusworth, Linda; Doebler, Stephanie; Ford, David; Griffiths, Lucy (International Journal of Population Data Science, 2024)
Introduction When a child has suffered, or is at risk of suffering, significant harm from parents or caregivers, the local authority may issue Section 31 (s.31) Care and Supervision proceedings under the Children Act (1989). Objectives We compared the healthcare use of infants less than one year old subject to s.31 proceedings in Wales (n = 1,332),to that of a comparison group of infants not subject to s.31 proceedings (n = 204,417), between January 2011 and February 2020. Methods Population-based e-cohort study utilising data held in the Secure Anonymised Information Linkage (SAIL) Databank. Infants in s.31 proceedings were identified using the Children and Family Court Advisory and Support Service dataset. This was linked to demographic and healthcare datasets, to identify General Practice (GP) visits, emergency department (ED) attendances, and hospital admissions (emergency and elective); before the study end date or the child's first birthday for the comparison group, orbefore the s.31 application date.Regression analysis calculated event rate ratios [RR] and incidence rate ratios [IRR] for healthcare events, adjusting for widerdeterminants of health (e.g. perinatal factors, maternal mental health, deprivation), and investigated reasons for healthcare use. Results Infants in s.31 proceedings had ahigher number and incidence of healthcare events compared with the comparison group, across all healthcare settings. Differences were greatest for emergency hospital admissions (IRR = 4.03, 95% confidence interval [CI] = 3.53 - 4.59; RR = 4.60, CI = 3.90 - 5.41). "Injury and poisoning" was the main reason for emergency admissions amongst infants in s.31 proceedings. For ED presentations, emergency hospital admissions, and GP visits, there were proportionally more events for these infants across all top ten reasons for healthcare. Conclusions Findings highlight greater healthcare utilisation for infants involved in s.31 proceedings in Wales, helping to build a better understanding of their needs and vulnerabilities.